2020
DOI: 10.1093/burnst/tkaa031
|View full text |Cite
|
Sign up to set email alerts
|

Assessing keloid recurrence following surgical excision and radiation

Abstract: Keloids are a fibroproliferative disorder that can result from a cutaneous injury to the reticular dermis. Recurrence rates as high as 100% have been reported following surgical excision alone. Consequently, a variety of post-surgical techniques have been employed to prevent keloid recurrence, including the use of radiation. Although numerous studies have shown post-excisional X-rays, electron beam, lasers and brachytherapy can reduce the rate of keloid recurrence, numerous inconsistencies, including a wide ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 64 publications
0
30
0
Order By: Relevance
“…There are multiple delivery methods in use, including X-rays, electron beam, lasers, and brachytherapy. 5…”
Section: Introductionmentioning
confidence: 99%
“…There are multiple delivery methods in use, including X-rays, electron beam, lasers, and brachytherapy. 5…”
Section: Introductionmentioning
confidence: 99%
“…As benign skin fibroproliferative tumors, keloids are characterized by a typical fibrosis state and some cancer-like features (Gold et al, 2020). A previous study has reported that circRNAs participate in the progression of fibrosis in various organs, including the skin, heart, liver, lung, and kidney (Dong et al, 2021;Wan et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Keloids can invade surrounding healthy skin out of the original wound, usually causing pain, severe itch, malformation, and even dysfunction, seriously affecting the physical and mental health of patients (Bijlard et al, 2017). Therapeutic options for keloids are few and ineffective with common recurrence and deformities posttherapy (e.g., surgery, drug injection, and perioperative radiation therapy) (Qu et al, 2013;Gold et al, 2020;Lv et al, 2020). Therefore, there is an urgent need to explore and understand the aggressive progression of keloids to help identify novel effective treatment strategies and preventive methods.…”
Section: Introductionmentioning
confidence: 99%
“…Keloid is accompanied by chronic inflammation, which is prone to infection and ulceration. At present, the main treatment for keloids is surgical resection, but there is a high recurrence rate after surgical resection alone, so it is often necessary to combine other adjuvant treatments after surgical resection ( 131 ). Surgical resection combined with radiotherapy is a more conventional treatment for keloids.…”
Section: Clinical Practicesmentioning
confidence: 99%